ANALISIS KELAYAKAN USAHA BUDIDAYA IKAN LEMAK DALAM KERAMBA DI DESA TANJUNG BELIT AIRTIRIS KECAMATAN KAMPAR KABUPATEN KAMPAR - Limetry Liana; Saipul Bahri; Tibrani Tibrani (DINAMIKA PERTANIAN, 2014)
This study aims to determine the use of input, the amount of costs, revenues, profits and BEP and to analysis financial feasibility of fish farming in cages fat. The research was conducted a survey method, located in Tanjung Belit Airtiris Village Kampar District Kampar Regency from June to November 2010. The total of 30 samples was selected purposively. The results showed that the total cost of production the fatty fish farming in cages is much Rp.365,718.36/m3/year, which consists of variable cost of Rp.214,093.19/m3/year and fixed cost of Rp.151,625.17/m3/year. Average of the resulting production amounted 18.78 kg/m3/year the acceptance value of Rp.394,316.00/m3/year and a profit of Rp.28,597.64/m3/year with BEP as much as 15.79 kg or Rp.329,619.93. Calculation of the three criteria, investment NPV, Net B/C ratio, and IRR in fatty fish, cultivated by farmers is feasible to be developed. It can be seen from 6% NPV of Rp.127,281.95, Net B/C ratio of 1.12 and IRR of 43,30%. Furthermore, based on the results of the analysis using a common market interest rate of 13% obtained NPV of USD 56,223.97/m3, Net B/C ratio of 1.10 and an IRR of 34.08%.